Exhaust emission of waste plastic disposal fuel on single cylinder YANMAR diesel engine - Mohd Hazmie, Hamdan (2010)
This report deals with the exhaust emission of waste plastic disposal fuel on single cylinder YANMAR diesel engine. The objectives of this report are to analyze the fuel consumption and the emission characteristic of a single cylinder diesel engine that are using waste plastic disposal fuel compared to usage of ordinary diesel that are available in the market. This report describes the setups and the procedures for the experiment which is to analyze the emission characteristics and fuel consumption of YAMNAR diesel engine due to usage of the both fuels. The experiment used diesel engine with no load which means no load exerted on it. Detail studies about the experimental setup and components have been done before the experiment started. Data that are required for the analysis is observed from the experiments. Calculations and analysis have been done after all the required data needed for the thesis is obtained. The obtained data indicated that the diesel fuel is better than waste plastic disposal fuel in term of fuel consumption, emissions of carbon monoxide (CO) and emissions of carbon dioxide (CO2). By the end of the report, the successful of the project have been stated which is YANMAR engine is able to run with waste plastic disposal (WPD) fuel but the engine needs to run by using diesel fuel first, then followed by waste plastic disposal fuel and finished with diesel fuel as the last fuel usage before the engine turned off.